Green synthesis of granular activated carbon/zinc ferro nanocomposites-based bioleached laterite iron (BLaFe) for the removal of Rhodamine B in water using adsorption–Fenton's oxidation process. Issue 3 (15th February 2023) - S., Bhaskar; K. N., Rashmishree; B., Manu; Sreenivasa, M. Y.
Abstract: Novel cost-effective catalyst granular activated carbon (GAC)-based zinc ferro nanocomposites for the heterogeneous Fenton's oxidation of dye were synthesized using bioleached laterite iron (BLFe) as a precursor and Psidium gujava leaf extract. Synthesized nanocomposites were characterized using SEM, EDS, XRD and BET surface area analysis. The degradation of Rhodamine dye was carried out with nanocomposites using adsorption–Fenton's oxidation process. The catalytic role of nanocomposites in Fenton's oxidation of Rhodamine B (RhB) was investigated and reported. The maximum dye removal of 96.2% was observed with 64.2% COD removal within 200 min of treatment. An increase in nanocomposite dosage has a positive effect on dye removal marking 5 g/L as an optimum dosage. Adsorption studies reveal that RhB removal using BLFe-based GAC/zinc ferro composites fits the Freundlich Adsorption Isotherm model with an adsorption capacity of 47.81 mg/g. A combination of adsorption and Fenton's oxidation has resulted in higher removal efficiency with nanocomposite material. Reusability studies confirm that the spent catalyst can be reused for five cycles. HIGHLIGHTS: Synthesis of novel GAC–zinc ferro composites. Characterization of synthesized nanocomposites. Removal of Rhodamine B using adsorption–Fenton's oxidation process. Graphical Abstract